PENERAPAN SISTEM AMONG DALAM PROSES PENDIDIKAN SUATU UPAYA MENGEMBANGKAN KOMPETENSI GURU - Siti Masitoh; Fibria Cahyani (Balai Besar Guru Penggerak Jawa Timur, 2020)
Professional teachers were required having four competencies as mandated by Teachers Law No. 14 of 2005. Those competencies were: (1) pedagogic, (2) professional, (3) personal, and (4) social competence. They seemed to Ki Hajar Dewantara's thoughts were explicitly reflected in Tamansiswa principles, namely: (1) orderly speaking and acting, (2) greetings, (3) peace, and (4) happiness. They accord to regulation of national education minister No. 16 of 2007, including